2015
DOI: 10.4238/2015.may.11.3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes associated with the biosynthetic pathways of abscisic acid, gibberellin, and ethylene during the germination of lettuce seeds

Abstract: ABSTRACT. Seed germination and dormancy are complex phenomena that are controlled by many genes and environmental factors. Such genes are indicated by phytohormones that interact with each other, and may cause dormancy or promote seed germination. The objective of this study was to investigate gene expression associated with the biosynthetic pathways of abscisic acid (ABA), gibberellic acid (GA), and ethylene (ET) in dormant and germinated lettuce seeds. The expressions of LsNCED, LsGA3ox1, and ACO-B were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Contreras et al (2009) found high levels of endogenous ABA in lettuce (Lactuca sativa 'Tango') seeds during the intermediate and late developmental stages, which correspond to the point when seeds become tolerant to desiccation. Clemente et al (2013) also obtained the same results for lettuce seeds, in which the expression of the LsNCED gene was higher during the late developmental stages. A similar increase in gene expression was observed in this study for dried seeds harvested during the more advanced developmental stages; however, the relative values were lower.…”
Section: Discussionsupporting
confidence: 65%
“…Contreras et al (2009) found high levels of endogenous ABA in lettuce (Lactuca sativa 'Tango') seeds during the intermediate and late developmental stages, which correspond to the point when seeds become tolerant to desiccation. Clemente et al (2013) also obtained the same results for lettuce seeds, in which the expression of the LsNCED gene was higher during the late developmental stages. A similar increase in gene expression was observed in this study for dried seeds harvested during the more advanced developmental stages; however, the relative values were lower.…”
Section: Discussionsupporting
confidence: 65%
“…In the present study, it was observed a negative relationship between CaABI 3 expression in the embryo and seed physiological quality, especially in seeds coming from harvested fruits in cherry stages, which had high germination values and low levels of CaABI 3 expression. This result was also observed in seeds of different species like Arabidopsis (Reyes & Chua, 2007), lettuce (Clemente et al, 2013), beet (Hermann et al, 2007) among others.…”
Section: Resultssupporting
confidence: 68%
“…This indicates a repression mechanism of coffee seed germination in early stages of development (Eira et al, 2006). This mechanism can be controlled by several factors, such as the balance of abscisic acid and gibberellins levels, as observed in other species, maintaining both embryo and seed in the development mode (Eira et al, 2006, Hermann et al, 2007Kanno et al, 2010;Clemente, et al, 2013).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Clemente et al (2015) studied the expression of genes associated with biosynthetic pathways of abscisic acid, gibberellin and ethylene during lettuce seeds germination and found genes exclusive of dormant seeds.…”
Section: Figure 1 Germination Speed Index (Gsi) Of Parsley Seeds Of mentioning
confidence: 99%